Home in the Poetry of Saudi Arabia Poets: Taher Zamakhshari an Example of a Distinguished Arab - Dahami, Yahya Saleh Hasan (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
Poets frequently extol and admire their own lands. Home is a very important topic for Saudi poets, Arab poets, and, I would venture to say, for every intellectual person. The same topic was directed by a number of Saudi poets, who provided us with beautiful lyrical poetry works honoring the Kingdom of Saudi Arabia, their country of origin. The study uses Taher Zamakhshari's poem "My Homeland" to highlight the poet's talent, awareness, and competency while also demonstrating his passion and allegiance toward the great nation. By referencing literary metaphors, images, and symbols in his poetry understudy, it makes a real effort to value, evaluate, and appraise the poet's skill and ability. Beginning with a brief discussion of poetry and its importance, the study then takes a look at Saudi poetry before returning to the career of the Saudi poet, Taher Zamakhshari. The critical-analytical-descriptive approach to the poem "My Homeland" is the main question and probe of the study. This approach is used in the paper, which pays close attention to the idea of the homeland because it is the main subject. After that, the article concludes with a conclusion.